Pemaknaan Jimat Sebagai Simbol Religi Bagi Mahasiswa Jepang - Fatonah Fatonah (Program Studi Ilmu Komunikasi FISIP Universitas Syiah Kuala, 2018)
This research started with the idea that many Japanese are not concerned with religious status. The Ippen monks in the 13th century made the concept of religion simpler for Japanese society through the use of amulets as religious symbols that were finally accepted by Japanese society. This study aims to determine the meaning, motives, and influence of amulets on the attitude and behavior of Japanese using qualitative methods with phenomenology approach and the theory of symbolic interaction. Data analysis techniques were in-depth interviews, participant observation, and documentation. The results of this study show that the amulets have a deep meaning including happiness, academic achievement, safety travel, health, success, and security. While the reason for having an amulet is to avoid danger and maintain safety, grow self-esteem, pass the test, be able to enter university, as a guard and protector, or to find a partner to get married. Religion, sex, and age influence Their attitude and behavior in the meaning of amulets. So it can be concluded that the view of the Japanese on the meaning of religion is not so important. They still carry God in their lives through the simplest way of omamori as a religious symbol in their self-concept.